Numerical FEA parametric analysis of CAI behaviour of CFRP stiffened panels - Gaitanelis, Dimitrios G.; Giannopoulos, Ioannis K.; Theotokoglou, Efstathios E. (Elsevier, 2019)
This paper examined the effect of numerical modelling parameters on the accuracy and computational efficiency of Carbon Fibre Reinforced Polymer (CFRP) stiffened panels under Compression After Impact (CAI). Pristine and damaged CFRP stiffened panels were subjected to compression in Abaqus® software using Cohesive Zone Model (CZM) method. Various case studies were examined and the effect of the stiffness parameters of the cohesive elements was critically assessed. Moreover, the required number of cohesive zones to fully capture the damage mechanisms of the impacted and pristine panels under compressive loading was examined. The results showed that a wrong set of parameters can even lead to neglecting the induced damage and can cause severe convergence problems in the numerical model. The importance of the Overall Meshing Factor (OMF) was highlighted and a user-defined subroutine (USDFLD) was applied to capture the decrease in the load bearing capability of an impacted panel prior to the compressive loading, since CZM was found insufficient for this scope. The above-mentioned remarks illustrated the process of investigating the optimum numerical parameters set to achieve an accurate and efficient finite element modelling of the stiffened panels structural performance and maximum load-carrying capability, when subjected to CAI loading.
Keywords: Delamination; Damage mechanics; Finite element analysis; Cohesive zone model (CZM)